The impact of digital technology on traditions and social life in Papua - Kowira, Gracia Cornellia; Ernawati, Paulina (Digital Theory, Culture & Society, 2025)
This article delves into how digital advancements have influenced the customs and societal interactions in Papua a province known for its culture and distinct social frameworks. It emphasizes the way in which enhanced connectivity via devices and the web has revolutionized communication channels economic prospects and cultural customs. Although digital innovations bring about advantages, like information access and business prospects the changes present issues concerning the conservation of traditions and disparities, in society. Based on research and findings, from sources this article seeks to offer a thorough insight into how digital technology plays a dual role, in influencing modern life in Papua.